(untitled) (Fiep Bulletin - online, 2024)
Tand Psychomotricity thinking about its origin, its concepts and its purpose. Therefore, we draw as a general objective of this study, to raise awareness of the importance of psychomotricity in Early Childhood Education. Followed by the respective specific objectives: to present the benefits of psychomotricity in Early Childhood Education; to diagnose the gaps in the children’s maturation process, when psychomotor activities are not developed according to the age group and to historically contextualize psychomotricity and its purpose. The research problem will start with the main aspects of Psychomotricity, seeking to understand a little of its history and how it emerged. Soon after, the contributions of Psychomotricity to learning will be exposed, what is its relationship with human development and with Children’s Physical Education. Psychomotor education works to prevent learning difficulties in reading, writing, laterality, socialization, among others. A child’s learning depends on the conditions provided by the social environment they live in, biological conditions, among other factors. The child goes through different stages in his growth, with different aspects, characterizing his relationships with the physical and mental world. To promote this, the presented Ebook comes to help but the difficulty that many professionals find when working with Psychomotricity, ten (10) activities were selected for each element addressed. Key-words: Psychomotricity. Physical education. Human development.